1998
DOI: 10.1068/p270105
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Hearing in Children with Visual Disabilities

Abstract: A study is reported of the effect of early visual experience on the development of auditory space perception. The spatial hearing of thirty-five children with visual disabilities (twenty-two with congenital total blindness) was compared with that of eighteen sighted children and seventeen sighted adults. The tests provided a comprehensive assessment of spatial-hearing ability, including psychophysical estimates of spatial resolution in the horizontal, vertical, and distance dimensions, as well as measures of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
62
3
5

Year Published

2001
2001
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(81 citation statements)
references
References 44 publications
11
62
3
5
Order By: Relevance
“…This also agrees with the observations that blind listeners are at least comparable and usually slightly better than sighted listeners in performing localization task (Ashmead et al, 1998;Lessard et al, 1998;Starlinger and Niemeyer, 1981;Simon et al, 2002). The point of view that general visibility of surroundings is usually not helpful in auditory localization task is further supported by who reported that short-term (90 min) light deprivation prior to the localization task improves localization accuracy (but not localization precision; see section 5).…”
Section: Vision and Memory Cuessupporting
confidence: 79%
“…This also agrees with the observations that blind listeners are at least comparable and usually slightly better than sighted listeners in performing localization task (Ashmead et al, 1998;Lessard et al, 1998;Starlinger and Niemeyer, 1981;Simon et al, 2002). The point of view that general visibility of surroundings is usually not helpful in auditory localization task is further supported by who reported that short-term (90 min) light deprivation prior to the localization task improves localization accuracy (but not localization precision; see section 5).…”
Section: Vision and Memory Cuessupporting
confidence: 79%
“…We have argued that a point in space can be identified by the organism based on the observation that different acoustic inputs originated from the same relative spatial location show similar changes to motor actions. We employ this assumption because there is considerable evidence provided by studies on blind subjects suggesting that sound localization can develop without the help of another distal exteroceptive sense such as vision (Ashmead et al, 1998;Lewald, 2002). However, we fully recognize the potential importance of vision, when available.…”
Section: Multi-sensory Nature Of Spatial Hearingmentioning
confidence: 99%
“…Examination of localization precision as a function of source location by Röder et al (1999) found comparable results in the frontal direction and improved localization for more lateral sounds in blind subjects. Ashmead et al (1998), in addition to providing a thorough bibliographic study on spatial audition studies, presented a study comparing Minimum Audible Angle (MAA) for azimuthal changes around positions at 0 • and 45 • and elevation changes at 0 • , and Minimum Audible Distance (MAD) thresholds. Test protocol used a 2-down 1-up staircase method.…”
Section: Spatial Auditory Perception Of the Visually Impairedmentioning
confidence: 99%